2000
DOI: 10.1177/002204260003000105
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effects of Interviewer Characteristics in an RDD Telephone Survey of Drug Use

Abstract: Although a small number of studies are available that evaluate the effects of Interviewer characteristics in substance use surveys conducted in person, none have done so using information collected via telephone interviews. We address this issue by examining the utility of social attribution and social desirability models for detecting the presence of Interviewer effects In a large statewide telephone survey concerned with substance use. The specific outcome variables ofinterest were reports oflifetime and 18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
(18 reference statements)
0
26
0
Order By: Relevance
“…Johnson et al (42) found that increased social distance between respondent and interviewer (i.e. decreased respondent-interview similarity) decreased the probability of respondents reporting lifetime and recent substance use behaviour in a telephone survey.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al (42) found that increased social distance between respondent and interviewer (i.e. decreased respondent-interview similarity) decreased the probability of respondents reporting lifetime and recent substance use behaviour in a telephone survey.…”
Section: Discussionmentioning
confidence: 99%
“…There are two common approaches for analyzing interviewer effects: the Social Attribution Model and the Conditional Social Attribution Model (Fendrich et al, 1999;Johnson et al, 2000). In the first approach, interviewer characteristics have a direct effect on individual responses in the sense that -respondents evaluate interviewers and make inferences about their norms, values, and beliefs based upon their observable characteristics‖ and may -tailor their answers in an effort to elicit interviewer approval by conforming to their perceived expectations‖ (Fendrich et al, 1999).…”
Section: Williams 1964and1968)mentioning
confidence: 99%
“…The greater the social distance between respondent and interviewer, the more likely a respondent alters her answer to conform to the interviewer. Social distance is usually measured in terms of differences or similarities in the social identities of interviewers and respondents (Johnson et al, 2000). For instance, the social distance of an interviewer and a respondent is smaller when they are of the same gender.…”
Section: Williams 1964and1968)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that the reason is a shorter social distance between the interviewer and the respondent, a hypothesis propounded by previous research (Kuebler and Hausser 1997, Johnson et al 2000, Williams and Nowatzki 2005. Another possibility is that the respondents did not try to hide certain sensitive behaviors from the PAIs since they, by virtue of their acquaintanceship, already knew that the PAIs had prior knowledge of them.…”
Section: Discussionmentioning
confidence: 98%